Challenges and Strategies in Managing Inclusive Education for Children with Special Needs in Primary Islamic Schools - Ratna Sari; Nurlaila Nurlaila; Istiarsyah Istiarsyah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to examine the challenges and strategies in managing inclusive education for children with special needs in primary Islamic schools through a thematic literature review. Using a thematic synthesis approach, this study systematically reviewed and analyzed relevant national and international peer-reviewed literature focusing on inclusive education, school management, and Islamic education contexts. The analysis identified five interrelated themes: teacher capacity and pedagogical readiness, institutional readiness and school management, curriculum and instructional adaptation, resource availability and support systems, and values-based and collaborative strategies. The findings indicate that challenges in inclusive education are systemic rather than isolated, requiring coordinated management responses rather than fragmented interventions. Importantly, the review highlights those Islamic values such as justice (‘adl), compassion (rahmah), and collective responsibility serve as ethical foundations that can strengthen leadership commitment and sustain inclusive practices. Based on these findings, this study proposes a Holistic Management Framework for Inclusive Education in Primary Islamic Schools, which integrates pedagogical, institutional, managerial, and ethical dimensions. The study contributes to inclusive education literature by offering a contextually grounded framework that supports the effective and sustainable management of inclusive education in faith-based primary schooling.